Riddah dan HAM dalam Tinjauan Hukum Islam: Apostasy and Human Rights in the Perspective of Islamic Law - Rosdiana Rosdiana (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2005)
The phenomenon of religious conversion from Islam (riddah) has long provoked persistent legal and theological controversy over its compatibility with international human rights standards. Islamic legal tradition presents a paradox between Qur'anic affirmations of free religious choice and classical fiqh sanctions, including capital punishment for apostates. This study critically examines the conceptual relationship between riddah and human rights within Islamic jurisprudence. Using a qualitative library research method with content analysis, it analyzes primary sources from the Qur'an and hadith, as well as secondary sources, including classical and contemporary scholarly works. The findings reveal that the death penalty for riddah arose from specific historical contexts of political treason rather than purely religious apostasy, and that classical jurists required strict evidentiary standards and opportunities for repentance before execution. Furthermore, contemporary Muslim scholars argue that such punishment contradicts Qur'anic principles of no compulsion in religion. The study concludes that applying capital punishment for individual religious conversion is incompatible with contemporary human rights frameworks and suggests that Muslim societies should reexamine traditional rulings by prioritizing absolute Qur'anic texts over hadith with speculative authenticity, while distinguishing between apostasy as a private religious act and treason as a public offense. Fenomena perpindahan agama dari Islam (riddah) telah memicu kontroversi hukum dan teologis yang berkelanjutan terkait kesesuaiannya dengan standar hak asasi manusia internasional. Tradisi hukum Islam menunjukkan paradoks antara penegasan Al-Qur'an tentang kebebasan memilih agama dan sanksi fiqh klasik yang mencakup hukuman mati bagi pelaku riddah. Penelitian ini bertujuan untuk mengkaji secara kritis hubungan konseptual antara riddah dan hak asasi manusia dalam perspektif hukum Islam. Menggunakan metode penelitian kepustakaan kualitatif dengan analisis isi, penelitian ini menganalisis sumber primer dari Al-Qur'an dan hadis serta sumber sekunder berupa karya ulama klasik dan kontemporer. Temuan penelitian mengungkapkan bahwa hukuman mati bagi riddah berasal dari konteks historis pengkhianatan politik, bukan semata-mata kemurtadan agama, dan ulama klasik mensyaratkan bukti yang ketat serta kesempatan bertobat sebelum eksekusi. Lebih lanjut, ulama kontemporer berargumen bahwa hukuman tersebut bertentangan dengan prinsip Al-Qur'an tentang tidak ada paksaan dalam agama. Penelitian menyimpulkan bahwa penerapan hukuman mati untuk konversi agama individu tidak sesuai dengan kerangka HAM kontemporer dan merekomendasikan agar masyarakat Muslim meninjau ulang aturan tradisional dengan memprioritaskan teks Al-Qur'an yang mutlak atas hadis yang bersifat zhanni, serta membedakan antara riddah sebagai tindakan agama pribadi dan pengkhianatan sebagai kejahatan publik.